Macroscopic determination of the pre-burning condition of human remains recovered from an unusual forensic context: A case report. (February 2021) - Monetti, Lisa; Voulgari, Myrsini; Karagiorgou, Ioanna; Moraitis, Konstantinos
Abstract: Understanding the taphonomic process of burning allows forensic practitioners to better interpret remains and reconstruct the burning incident in a medicolegal investigation. This can yield critical information, especially when other details, such as the biological profile, are obscured by fire. A forensic case involving human remains recovered within a Greek Orthodox cemetery that exhibited a distinctive pattern of differential burning is reported. The bones exhibited a range of differential burning in a pattern inconsistent with the anatomical position of the remains during heat exposure. No macroscopic signs of skeletal trauma or evidence of dismemberment were present on the remains. The pre-burning condition of the bones was inferred based on the presence of the differential burning and its localization identified through analysis of a suite of macroscopic heat-induced traits, as well as consideration of the forensic context. The anthropologists concluded that the bones were skeletonized prior to burning and that the remains were once interred or stored in an ossuary and were likely burned in a ritualistic manner, given the artifacts present and the conspicuous location of the burn area. This case highlights the practical experience required of forensic practitioners encountering burned remains and the necessity of understanding fire as a taphonomic agent that can be analyzed to determine pre-burning condition and the scenario of the burning event in a medicolegal investigation. Furthermore, this case underscores the achievability of pre-burning condition determination using macroscopic traits alone, even when there is a paucity of skeletal elements in the inventory. Due to knowledge of the funerary customs of modern-day Greece, the practitioners were able to interpret the origin of the remains, thereby this paper provides insight into a geographically specific forensic context. Highlights: Pre-burning condition can be implied using macroscopic heat-induced traits. No particular trait can be used alone to confirm the pre-burning condition. The specific context of the remains should be considered during the investigation. Forensic experts must be aware of typical burn patterns seen on skeletal remains.